Detection of Listeria sp in meat and meat products using TECRA Listeria visual immunoassay and biocontrol visual immunoprecipitate assay for Listeria immunoassays and a cultural procedure - Aragon-Alegro, L. C.; Wittmann, R. M.; Padovani, C. R.; Landgraf, M.; Franco, BDGD; Destro, M. T. (Blackwell Publishing, 2005)
The routine methods for detecting Listeria sp. in foods are time consuming and involve using selective enrichments and plating on agars. In this study, the presence of Listeria sp. in 120 meat and meat product samples was investigated by two rapid immunoassays (TECRA Listeria Visual Immunoassay [VIA] and BioControl Visual Immunoprecipitate Assay [VIP] for Listeria) and a cultural procedure. The cultural method of detecting Listeria sp. followed Canada's Health Protection Branch Method, and the rapid tests followed the manufacturers' instructions. The agreement between the cultural and the rapid tests was established at a confidence limit of 95%. Seventy-nine samples (65.8%) were Listeria sp. positive in at least one of the three tests. There was no statistically significant difference between the cultural procedure and any of the rapid immunoassays. The agreement rates between the VIA and the cultural method and between the VIP and the cultural method were 87 and 84%, respectively. Both tests - the VIA and VIP - proved to be rapid, efficient and easy to perform.